MORE THAN A HOUSE: A GENDER ANALYSIS OF LAHSA’S THE VIOLENCE AGAINST WOMEN ACT (VAWA) HOUSING POLICY - Listiyanti Jaya Arum; Anindya Firda Khairunnisa (Rubikon : Journal of Transnational American Studies, 2021)
Homelessness is a chronic problem worldwide, including in the United States. The country’s biggest homeless population occupies major cities like New York and Los Angeles. The fight against homelessness in L.A. has been going on for years, with the homeless population flooding places like Venice Beach, Echo Park, Hollywood, and its most famous homeless encampment, Skid Row. One of the groups constantly vulnerable to the threat of homelessness are women, and the intersection between women's homelessness and domestic violence remains to be a challenging subject. Enriching previous scholarship, this paper critically analyzes housing programs targeting female domestic violence survivors in Los Angeles. In order to get an in-depth examination, the focus is directed to the Violence Against Women Act (VAWA) Housing Policy managed by the Los Angeles Homeless Services Authority (LAHSA). The paper employs gender theory to examine the program’s shortcomings. Using Jeff Hearn’s conception of the ‘public men,’ this paper proposes that the program’s limitations stem from the prevailing patriarchy, which cultivates from home and extends to public policy through the domination of men. Furthermore, the policy is insufficient in combatting women's homelessness due to the absence of programs such as trauma centers, financial security & education program, and childcare unit that are vital to address the unique experience of domestic violence survivors. Thus, evaluation of the housing policy is immediately needed to overcome the problem of homelessness due to domestic violence.